A Parameter Sensitivity Analysis of the Effect of Rebar Corrosion on the Stress Field in the Surrounding Concrete - Fangyuan Li; Wenya Ye (Advances in Materials Science and Engineering)
Rebar corrosion results in a change in the stress field in the surrounding concrete, which in turn accelerates the deterioration of the concrete structure. In addition to the protective layer, the compressive stress under which concrete is prestressed also affects the effect of corrosion-induced rebar expansion on the stress field in the concrete. The present study simulates the effect of corrosion-induced rebar expansion on the stress field in the concrete using the finite element method (FEM) by applying a virtual radial displacement to the product of corrosion-induced rebar expansion. Based on an analysis of the effect of multiple rebars on the stress field in ordinary concrete, stress distribution in the protective layer of the concrete is determined. Afterward, the locations where there is damage to the surface concrete caused by rebar corrosion are determined. After verifying the feasibility of the FEM analysis, the effect of corrosion-induced ordinary rebar expansion in a typical prestressed concrete segment is determined by analyzing the characteristics of corrosion-induced rebar expansion occurring in various prestressed concrete specimens.